A Study on the Inheritance and Differentiation of Spatial Forms of Vernacular Architecture in the Yunnan–Tibet Area - Kua Wu; Haowei Wang; Heng Liu; Man Yin; Junhua Xu; Mingli Qiang; Yanwei Su (Buildings, 2025)
Vernacular architecture is a complex and living heritage type, and the study of the evolution laws of its spatial form is of great value to the conservation of architectural heritage diversity. Taking vernacular architecture in the Yunnan–Tibet area as the research object, based on the theory of spatial syntax, 30 building samples were subjected to global and local calculations of MD, IRRA, and NACH values, while the common characteristics among the samples were obtained by using Kendall’s W test, and the individual characteristics among the samples were obtained by using differentiation analysis. The results show that: (a) vernacular architecture in the Yunnan–Tibet area exhibits characteristics of multi-cluster branched centrality and spatial hierarchical layout; (b) these architectures possess four categories of inheritance factors: the privacy of granary spaces, the centrality of corridor spaces, the passability of breeding areas, and the independence of scripture hall spaces; (c) these architectures possess three categories of differentiation factors: the functional evolution of traditional spaces, the spatial reconstruction of breeding areas, and the “Toilet Revolution” driven by multiple forces. This study elucidates the regulatory role of cultural continuity in shaping the spatial forms of vernacular architecture, providing new evidence for analyzing the formation mechanisms of vernacular architecture in the Yunnan–Tibet area.